Preliminary study on the production of common carp cultured in freshwater river cages (International Journal of Agricultural Research, Innovation and Technology, 2014)
A preliminary study was conducted to assess the performance of the common carp, cultured in freshwater river of Brahmaputra cages at different stocking densities during November 2011 to March 2012.The stocking densities tested were 80, 100 and 120 fish/m3. Fish were fed a 28% protein diet at the rate of 15-5% of body weight. The result of the study showed that fish in the T1 stocked at the rate of 80 fish/m3 resulted the best individual weight followed by T2 and T3. The productions of fish in T1, T2 and T3 were 22.33±1.20, 19.00±0.58 and 18.00±1.15 kg/m3, respectively. The results of the present study indicated that the best individual growth and production of common carp was obtained at a density of 80 fish/m3. The results also showed that the individual mean harvesting weights were negatively correlated with stocking density. Therefore, the stocking density of 80 fish/m3 is considered optimum for the rearing phase. DOI: http://dx.doi.org/10.3329/ijarit.v4i1.21086 Int. J. Agril. Res. Innov. & Tech. 4 (1): 24-27, June, 2014